Neighborhood watch : the rise of Zillow - Green, Joanna, (SAGE Knowledge. Cases., 2017)
Read any news report on the housing market, and inevitably it will include facts or figures from the real estate data giant Zillow.com. The company initially set out to solve two key economic frictions in the real estate industry--information asymmetry and the principal-agent problem--by empowering users to access real-time housing data and eliminating the need for realtors. The company soon realized, however, that American homeowners and buyers were not willing to give up the traditional real estate agent model and changed course. In the end, Zillow decided to join--rather than replace--the middlemen in the real estate industry.